Institutional sustainability of Panpacific University : interactive analysis - Catanes, Jimmy G. (Urdaneta City, Pangasinan : [s.n.], 2018)
The study aimed to determine nthe institutional sustainability of Panpacific University where defined by the Commission on Higher Education institutional sustainability is the organization's ability to address current educational needs and to have the agility and strategic management to prepare successfully for future educational, market, and operating environment. This study made use of the descriptive-evaluative research institutional frameworks. Evaluative research is concerned with the assessment of policies, programs or institutional frameworks. Evaluative research eveluates, judges, assesses or measures something in relation to outcomes or requirements (Wollman, nd) The rationale of this approach is to evaluate, validate and confirm the quantitative data to end up with valid and well-substantiated conclusions about the institutional sustainability of Panpacific University (Creswell, 2006).
Bibliography: pages 106-110.
CHED-La Union
Keywords: Colleges and universities; Education